The ROLE OF DAYCARE BOCAH EMAS IN STIMULATING THE SOCIAL DEVELOPMENT OF CHILDREN AGE 4-5 YEARS: THE ROLE OF DAYCARE BOCAH EMAS IN STIMULATING THE SOCIAL DEVELOPMENT OF CHILDREN AGE 4-5 YEARS - Shelfi Eka; Laily Rosidah; Cucu Atikah (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2023)
Early childhood is an individual who is in the age range of 0 to 6 years, this age range is the most qualified period to stimulate every aspect of development in children, especially in terms of aspects of social development. Children's social development is a series of social behaviors that appear in individuals. Generally, patterns of social behavior in children are obtained through social events received in their social environment. This research aims to determine the role of daycare in stimulating social development in children aged 4-5 years. In this case, researcher made aspects of social development, there are : aspects of cooperation, aspects of empathy, aspects of generosity, and aspects of imitation with indicators; play and cooperate with other friends, can put themselves in the position of others, can share with friends and people around daycare, and can practice worship activities. This type of research uses descriptive qualitative by data collection methods through observation, the results of interview and documentation in this research explained that the role of Bocah Emas daycare in stimulating social development in children aged 4-5 years has shown success in several aspects. The inhibiting and supporting factors for social development in children aged 4-5 years in the Bocah Emas daycare occur due to several factors, there are: home environment factors, family factors, social status factors and factors of child interaction with their friends.